Comparison of Software Testing Tools on Gui Features - Ghazali, Fatimah (2005)
Software testing is an important approach to software quality assurance. It is a kind of software development activity throughout all the life cycle of software development, whose purpose is to find the potential errors or bugs of software as many as possible. Hence, software testing tools were developed to assists software engineering to gauge the quality of software automating the mechanical aspects of the software testing tasks. Software testing tools vary in their underlying approach, quality and easeof- use among the other features. This project paper compares and measures three selected software testing tools that available in current market. These testing tools were downloading from Internet. Comparison of three selected testing tools based on graphical user interface (GUI) features and usability. The GUI features are proposed by Stephen Morris. The software testing tools also measured on usability aspect from user’s perspective to determine the efficiency, affect, helpfulness, control and learnability of software testing tools. The result of the study was to propose general features of GUI for software testing tools that should be considered in software testing tools.